Rearing pigs with play opportunities: the effects on disease resilience in pigs experimentally inoculated with PRRSV - Steinerová, Karolína; Harding, John C. S.; Parker, Sarah E.; Wilson, Heather L.; Nery Finatto, Arthur; Seddon, Yolande M. (Frontiers in Veterinary Science, 2024)
Positive emotions can reduce disease susceptibility during infectious challenges in humans, and emerging evidence suggests similar effects in farm animals. Because play behaviour may support a positive emotional state in pigs, this study investigates whether rearing pigs with regular intermittent play opportunities enhances disease resilience when challenged with porcine reproductive and respiratory syndrome virus (PRRSV). Litters were assigned to either play (PLY; n = 5 L) or control (CON; n = 4 L) treatments at birth. In PLY, play was promoted with extra space and enrichment items for three hours daily from five days of age (doa). At weaning (25 ± 2 doa; mean ± SD), 28 pigs (14/treatment) were selected for a disease challenge, based on weight, sex, and sow. The pigs were transported to a disease containment facility and at 43 ± 2 doa (day 0 post-inoculation, DPI) inoculated with PRRSV. Skin lesions, blood, rectal temperature, clinical signs, body weight, and behaviour were collected pre- and post-inoculation. Play opportunities for PLY continued every other day until euthanasia of all pigs at 65 ± 2 doa (22 DPI). PLY pigs exhibited fewer skin lesions following transport and throughout the infection compared to CON. Although the viral load did not differ between treatments, PLY pigs had a lower probability of experiencing moderate and severe respiratory distress, with a shorter duration. PLY also performed better throughout the infection, showing higher ADG and greater feed efficiency. The immune response differed as well. PLY pigs had fewer monocytes on 8 DPI than CON, with levels returning to baseline by 21 DPI, whereas CON levels exceeded baseline. Regardless of day of infection, lymphocyte counts tended to be lower in PLY than in CON, and white blood cells and neutrophils were also lower, but only in slow-growing pigs. PLY pigs continued to play during the infection, demonstrating less sickness behaviour and emphasizing the rewarding properties of play. Results suggest that PLY pigs were less affected by PRRSV and developed increased resilience to PRRSV compared to CON. This study demonstrates that rearing pigs in an environment supporting positive experiences through provision of play opportunities can enhance resilience against common modern production challenges, underscoring the value of positive welfare in intensive pig farming.